Pengaruh Gaya Belajar Audio terhadap Hasil belajar Pada Mata Pelajaran Bahasa Arab - norhidayah norhidayah09; Marsiah Marsiah; Aulia Mustika ilmiani (Taqdir, 2022)
Learning style is one of the factors that affect student learning outcomes. In the learning process, students have different learning styles. Learning style is a person's way to absorb, organize and process information or learning materials. This study aims to determine the effect of audio learning style on the learning outcomes of the students of the State Madrasah aliyah of Palangka Raya City. This research uses descriptive qualitative research. The sampling technique in this study was the researcher using Probability Sampling. The sample in this study amounted to 135 students. Data collection techniques in this study were researchers using questionnaires and documentation. Analysis in this study, researchers use SPSS. The results of this study, the researchers found that there was an effect of audio learning style on the learning outcomes of the students of Madrasah Aliyah Negeri Palangka Raya with significant results 0.00 > 0.05. So, it can be concluded that there is an influence of audio learning style on the learning outcomes of the students of Madrasah Aliyah Negeri Palangka Raya.